Analisis Efektivitas Sistem Resi Gudang Dalam Mengatasi Turunnya Harga Kopi Gayo Di Kabupaten Bener Meriah - cibro, ikhe sigemasih; Arif, Muhammad; Harahap, Muhammad Ikhsan (Universitas Muhammadiyah Sumatera Utara, 2022)
Warehouse receipts in this study focused on the benefits to farmers, such as applying for a loan from a financial institution (Bank or Not) that has signed a cooperation agreement (contract) to meet the financing needs of farmers. This study aims to determine the effectiveness of WRS in Bener Meriah Regency which is managed by CV.Pratama Gayo Mandiri to overcome the problem of the decline in the price of Gayo coffee seen from the suitability of goals, efficiency and group satisfaction. And to find out how the implementation of the Warehouse Receipt System in Bener Meriah Regency with a pattern of financing in collaboration with Islamic Bank financial institutions in accordance with established standards. determined by the Ministry of Commerce. The data in this study were collected through the distribution of questionnaires to 30 farmer group coffee collecting agents registered in the WRS Bener Meriah Regency. The analytical method used is qualitative analysis. The results of the analysis show that the effectiveness of the Warehouse Receipt System in terms of the accuracy of the objectives and results of the WRS implementation and its efficiency has been very effective, and from the perspective of farmer group satisfaction it is quite effective. determined by laws and regulations of the ministry of commerce.